Joan Baez : I am a noise [videorecording (DVD)] - Navasky, Miri; O'Boyle, Maeve; O'Connor, Karen; Baez, Joan; Shykind, Hanna; Baez, Joan, Sr., 1913-2013; Fariña, Mimi; Dylan, Bob, 1941-; Harris, David, 1946- (Magnolia Pictures, 2024)
Neither a conventional biopic nor a traditional concert film, this documentary is a raw and intimate portrait of the legendary folk singer and activist that shifts back and forth through time as it follows Joan on her final tour and delves into her extraordinary archive, including newly discovered home movies, diaries, artwork, therapy tapes, and audio recordings. Baez is remarkably revealing about her life on and offstage, from her lifelong emotional struggles to her civil rights work with MLK and a heartbreaking romance with a young Bob Dylan. A searingly honest look at a living legend, this film is a compelling and deeply personal exploration of an iconic artist who has never told the full truth of her life, as she experienced it, until now.